A new approach towards pathogenesis, diagnostics, natural course and complications of optic disc drusen - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
Optic disc drusen are the inherited changes, which occur in about 0,3% of the population. The optic discs of patients with drusen characteristically show a lumpy, bumpy border and bright irregular deposits. Drusen are generally asymptomatic, but in some cases visual defects occur. B-scan sonography, fluorescein angiography and computed tomography are the best imaging procedures for diagnosing of the optic disc drusen. Drusen are quite often associated with various vascular anomalies and complications. Patients with retinitis pigmentosa and angioid streaks have a higher prevelance of drusen. Although, no effective treatment of optic disc drusen has been established, regular examinations should be carried out in order, to recognize accompanying complications. This paper presents current knowledge on the pathogenesis, diagnostics, vascular changes and disorders associated with the optic disc drusen, as well as on their complications and management.